PERAN KEPEMIMPINAN TRANSFORMASIONAL DIGITAL KEPALA SEKOLAH DALAM MENCIPTAKAN BUDAYA INOVASI PENDIDIKAN ERA 4.0 - Rokimin; Dudun Ubaedullah; Nashiruddin; Taufik (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to explore the role of school principals in integrating technology into teaching and learning, the challenges encountered in the process, and the competencies required for principals to lead digital transformation. A qualitative method with a case study approach was employed in several schools in Indonesia. Data were collected through in-depth interviews with principals, teachers, and students, as well as document analysis related to school technology policies. The findings indicate that principals with a clear vision and adequate technological competence are able to foster the successful integration of technology in instruction. Key challenges include teachers’ resistance to change, limited resources and infrastructure, and the lack of ongoing professional development for teachers. Principals who address these barriers by providing sufficient support, continuous training, and cultivating a culture of innovation can accelerate schools’ digital transformation. Moreover, principals’ technological competencies play an important role in motivating and facilitating teachers to integrate technology. The study offers recommendations for principals to adopt transformational leadership and to place greater emphasis on teacher professional development and the enhancement of technological infrastructure. It is hoped that this research provides insights for education policymakers and school leaders to strengthen technology implementation in schools.